2018
DOI: 10.1093/infdis/jiy260
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Human Immunodeficiency Virus (HIV) Ribonucleic Acid in Cerebrospinal Fluid and Blood Is Linked to CD4/CD8 Ratio During Acute HIV

Abstract: The degree of central nervous system penetration by HIV at acute infection, measured by the viral load difference between plasma and cerebrospinal fluid, is highly variable and correlates with CD4/CD8 ratio, suggesting an underlying modifying role by individual immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
(47 reference statements)
3
13
0
Order By: Relevance
“…These findings are consistent with recent epidemiological reports about syphilis in other societies [2,13,25]. We previously reported that untreated syphilis had no measurable effect on CSF HIV-1 RNA levels in a subset of cohort participants who underwent optional LP for research purposes during untreated AHI [11]. The current analysis focused primarily on the effects of clinical parameters by syphilis, which compared individuals with any syphilis and untreated syphilis with those without any prior syphilis at the time of AHI.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These findings are consistent with recent epidemiological reports about syphilis in other societies [2,13,25]. We previously reported that untreated syphilis had no measurable effect on CSF HIV-1 RNA levels in a subset of cohort participants who underwent optional LP for research purposes during untreated AHI [11]. The current analysis focused primarily on the effects of clinical parameters by syphilis, which compared individuals with any syphilis and untreated syphilis with those without any prior syphilis at the time of AHI.…”
Section: Discussionsupporting
confidence: 89%
“…Participants included all 595 individuals enrolled into the SEARCH010/RV254 cohort (NCT00796146) between April 2009 and March 2019. The methodology and primary goals of the cohort study have been described elsewhere [11]. Briefly, these individuals enrolled in voluntary HIV counselling and testing services offered in Bangkok, Thailand, which systematically screened for AHI.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…As has been previously reported in this cohort [6,7,37], multiple soluble markers of inflammation were differentially expressed in CSF during acute HIV-1 infection. Among a panel of 44 pro-inflammatory cytokines and biomarkers measured by Luminex and ELISA in this subset of nine individuals, IL-10 (P<0.01), IP-10 (P<0.01), neopterin (P<0.01) and sCD163 (P<0.05) were ~2-5-fold elevated in CSF compared to PWOH.…”
Section: Plos Pathogenssupporting
confidence: 82%
“…Peripherally, CD8 + T cells exert some control of viral infection by cytotoxicity-mediated killing (5). In one study, these cytotoxic CD8 + and helper CD4 + T lymphocytes independently correlated directly with HIV RNA levels in cerebrospinal fluid (CSF) and in plasma during acute infection, suggesting that peripheral immune response may modulate CNS viral infection (6). However, the severity of CNS lesions did not correlate with the corresponding plasma viral load, despite the correlation between CSF and plasma viral loads (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%